Microstructure Characterisation and Modelling of Pre-Forging Solution Treatment of 7075 Aluminium Alloy Using Novel Heating Methods - Hao Wu; Zisong Lu; Steven Hill; Richard Turner (Journal of Manufacturing and Materials Processing)
This study evaluates the effectiveness of these conventional heating methods, commonly adopted in the industry with long durations (typically one hour), in comparison to newer, potentially more efficient approaches such as induction coil heating, infrared module heating, and infrared furnaces that can perform solution heat treatment in significantly shorter times (5 to 20 min). The properties of the edge and centre regions of the solution-treated billets, including the state of precipitates, grain structures, and Vickers hardness, are investigated and compared. Results have shown that the 7075 billets heated by conventional heating methods sufficiently dissolved the stable precipitates, achieving hardness ranging from 137 to 141 HV, in contrast to the benchmark unheated, as-received sample of approximately 70 HV. In the meantime, the induction coil and infrared furnace demonstrate notable effectiveness, achieving hardness between 126 and 135 HV. The average grain sizes in the centre and edge regions for all samples are measured as 3 and 8 µm, respectively. However, the impact of the grain size on the hardness is negligible compared to the impact of the precipitates. Finite element (FE) modelling comparing the slowest heating method—the electric furnace—and the fastest heating method—induction coil heating—reveals the latter could heat the billet up to 450 °C at a rate ten times faster than the electric furnace. This study highlights the potential of novel heating techniques in promoting the efficiency of heat treatment processes for 7075 aluminium alloys.